Eksplorasi Hati Kudus: Menelurusi Hubungan Spiritual Antara Hati Kudus Yesus Dan Karya Katekese Kongregasi Suster Katekis Hati Kudus - Florensia Imelda Seran (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This article aims to explore the spiritual connection between the Sacred Heart of Jesus and the catechetical work of the Congregation of Sisters of Catechists of the Sacred Heart. Through an in-depth research approach and theological reflection, this article explores the spiritual values ​​contained in the Sacred Heart of Jesus which can enrich the sisters' catechetical work towards the congregation. The Sacred Heart of Jesus and Catechesis have a significant relationship. This can be seen from the spiritual values ​​of the Sacred Heart of Jesus which can be used as catechesis material and have an impact on the growth and life of faith of the people. To achieve this goal, the author uses literature analysis. Through literature analysis in exploring the values ​​of the Sacred Heart of Jesus contained in the Holy Scriptures, Church teachings, the Constitution of the Congregation of the Catechist Sisters of the Sacred Heart and the spiritual experiences of the saints, the author finds that the spiritual values ​​of the Sacred Heart of Jesus can be integrated into the work of catechesis.